The Influence of Safety Compliance on Safety Climate with Safety Culture as a Mediator among Grab Drivers in South Jakarta - Basid, Rezqi Ananda; Yusuf, Muhammad Khaidir (Jurnal Manajemen Bisnis, 2024)
This study aims to analyze the influence of safety compliance, safety culture and safety climate among Grab drivers in South Jakarta. By gaining an in-depth understanding of these factors, it is expected that more effective safety strategies and programs can be developed to ensure the safety of both drivers and passengers, as well as to enhance security in future online transportation operations. The research employs a quantitative methodology with descriptive and inferential approaches. Data collection was conducted through questionnaires distributed to 98 Grab drivers in the South Jakarta area. The data were analyzed using SmartPLS 3.0 software with the Partial Least Square (PLS) method. The results of the study indicate a significant influence of safety compliance on safety culture, as well as on safety climate. These findings confirm that good safety compliance contributes to the formation of a strong safety culture and overall enhancement of the safety climate. Additionally, it was found that safety culture has a strong positive impact on safety climate.